Effects of sea ice retreat and ocean warming on the Laptev Sea continental slope ecosystem (1993 vs 2012) - Bienhold, Christina; Schourup-Kristensen, Vibe; Krumpen, Thomas; Nöthig, Eva-Maria; Wenzhöfer, Frank; Korhonen, Meri; Vredenborg, Myriel; Hehemann, Laura; Boetius, Antje (Frontiers in Marine Science, 2022)
The central Arctic Ocean is rapidly changing due to amplified warming and sea ice retreat. Nonetheless, it remains challenging to document and decipher impacts on key ecosystem processes such as primary production and pelagic-benthic coupling, due to limited observations in this remote area. Here we investigated environmental changes at the Laptev Sea continental slope (60-3400 m water depth) from the surface to the seafloor, by replicating sample transects two decades apart. Mean break-up of sea ice occurred earlier and mean freeze-up occurred later in 2012 compared to 1993, extending the ice-free period by more than 30 days. On average, observations and model results showed an annual increase in primary production of 30% and more in the study area in 2012. In contrast, calculated and modelled fluxes of particulate organic carbon (POC) to the seafloor were only slightly higher in 2012 and did not extend as far into the deep Laptev Sea as the increase in primary production, possibly due to a more developed retention system. Nevertheless, benthic surveys revealed a substantial increase in phytodetritus availability at the seafloor along the entire transect from the shelf edge to the deep sea. This calls for carbon input by lateral advection from the shelves, additional input from sea ice, and/or a late summer bloom. We also investigated the composition and activity of bacterial communities at the seafloor and potential linkages to the observed environmental changes. While bacterial abundance, biomass and overall community structure showed no systematic differences between the two contrasting years at all depths, extracellular enzymatic activities had increased as a result of higher food availability. This was partly reflected in higher benthic oxygen uptake, indicating a moderate impact on benthic remineralization rates at the time of sampling. Our results show considerable effects of ocean warming and sea ice loss on the ecosystem from the surface ocean to the seafloor in the Laptev Sea, which are likely to continue in the coming decades.